2004
DOI: 10.1016/j.ydbio.2004.03.012
|View full text |Cite
|
Sign up to set email alerts
|

A conserved enhancer element that drives FGF4 gene expression in the embryonic myotomes is synergistically activated by GATA and bHLH proteins

Abstract: FGF4 is the earliest member of the fibroblast growth factor (FGF) family expressed during embryogenesis where it plays essential roles in post-implantation development and limb growth and patterning. The expression of the Fgf4 gene in specific developmental stages, including the ICM of the blastocyst, the myotomes, and the limb bud AER, is regulated by distinct enhancer elements (Hom) in the 3' UTR. We previously identified the Hom3a region as the major DNA element responsible for Fgf4 expression in the myotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
16
1
Order By: Relevance
“…One possibility is that FOG-2 may be necessary for the cardiomyoblast to receive FGF signaling. Consistently, several interactions between FGF and GATA signaling have been identified (Xu et al 1999;Fossett and Schulz 2001;Bertrand et al 2003;Iwahori et al 2004;Murakami et al 2004).…”
Section: The Epicardium Acts As a Signaling Center For Heart Developmentmentioning
confidence: 54%
“…One possibility is that FOG-2 may be necessary for the cardiomyoblast to receive FGF signaling. Consistently, several interactions between FGF and GATA signaling have been identified (Xu et al 1999;Fossett and Schulz 2001;Bertrand et al 2003;Iwahori et al 2004;Murakami et al 2004).…”
Section: The Epicardium Acts As a Signaling Center For Heart Developmentmentioning
confidence: 54%
“…Indeed, we found that Fgf4 expression, which is regulated by MyoD Development 132 (6) Research article ∆KIM -GFP detected using a GFP probe (n=8/8); (I) GFP fluorescence. MKP3 regulates ERK MAPK activity in the dorsal sclerotome (Iwahori et al, 2004), was affected (Fig. 5H).…”
Section: Constitutive Activation Of Erk Map Kinase Results In Loss Ofmentioning
confidence: 98%
“…Musarò et al (1999) reported that the accumulated mRNA and protein levels of the GATA factor were increased in muscular cells during hypertrophy induced by IGF-1. It has been reported that the GATA box is necessary for skeletal and cardiac muscle-specific expression of myosin light chain 3 gene in rat (McGrew et al, 1996), and that the GATA factor synergizes with MyoD family to activate transcription of Fgf4 which is critical in early stage of skeletal muscle development (Iwahori et al, 2004). Meanwhile, the nucleotide sequence of GTCAAAT was found in the sequence of −916 to − 910 bp of MYH10 immediately downstream the GATA box (see Fig.…”
Section: Discussionmentioning
confidence: 95%